Precipitation and the Associated Moist Static Energy Budget off Western Australia in Conjunction with Ningaloo Niño - Zheng, Tao; Feng, Tao; Xu, Kang; Cheng, Xuhua (Frontiers in Earth Science, 2020)
Ningaloo Niño is a well-known ocean-atmosphere coupled climate event in the southeastern Indian Ocean that interacts with large-scale atmospheric circulations at the interannual time scale. When a Ningaloo Niño develops, remarkably enhanced precipitation anomalies occur primarily off the coast of northwestern Australia (NWA) rather than over the offshore area of western Australia (WA), where the most significant sea surface temperature warming prevails. This enhanced NWA precipitation manifests as jointly intensified stratiform and convective precipitation accompanied by an increase in high cloud cover. Further analyses of the column-integrated moist static energy (MSE) budget reveal that during Ningaloo Niño events, positive vertical MSE transport moistens and heats the atmosphere in the WA region. However, these moistening and heating effects are mostly offset by the inhibitory effect of the negative horizontal MSE advection, leading to the relatively weak and nonsignificant variation in local precipitation anomalies off the WA coastal region. In contrast, off the coast of the NWA region, the recharge of column-integrated MSE, which is induced by the significant positive radiative and surface heating, horizontal MSE advection, and vertical MSE advection, contributes to the heaviest austral summer precipitation associated with Ningaloo Niño. Therefore, the distinct MSE transport processes result in the particular rainfall pattern in which the most enhanced rainfall is associated with Ningaloo Niño events over the NWA region.